2022
DOI: 10.1115/1.4054969
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Artificial Intelligent in Risk-Based Inspection Assessment and Screening: A Study Case of Inline Inspection

Abstract: The work reports the systematic approach to the study of Artificial Intelligence (AI) in addressing the complexity of ILI data management to forecast the risk in natural gas pipelines. A recent conventional standard may not be sufficient to address the variation data of corrosion defects and inherent human subjectivity. Such methodology undermines the accuracy assessment confidence and is ineffective in reducing inspection costs. In this work, a combination of Unsupervised and Supervised Machine Learning and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Based on (6), A corresponds to the impacted area, and X is the continuous leakage rate and instantaneous leakage mass. The variables a and b are specified in the API 581 standard for the reference fluid of the API 581 standard handbook.…”
Section: 2 Risk-based Inspectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on (6), A corresponds to the impacted area, and X is the continuous leakage rate and instantaneous leakage mass. The variables a and b are specified in the API 581 standard for the reference fluid of the API 581 standard handbook.…”
Section: 2 Risk-based Inspectionmentioning
confidence: 99%
“…A company must reduce the hazard and impact of the risk posed in the event of a failure by implementing preventive steps to ensure that the pipeline's operation is maintained and safe in a more effective manner. The Risk-Based Inspection (RBI) method is one strategy that is thought to be effective in maintaining pipeline integrity [6,7]. Compared to the Time-Based Inspection approach, RBI is a method for developing an inspection plan based on the probability of failure during equipment operation and the impact if a failure occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, developing a deep learning model in corrosion mitigation has not been fully explored. Deep learning is the subset of machine learning that has been used successfully across various applications, including corrosion detection [18] and the risk assessment of pipelines [19]. Inclusively in the field of corrosion science, the application of artificial intelligence has been found on many fronts.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, regular pigging before corrosion inhibitor [ [14] , [15] , [16] ] injection is more effective in maintaining the integrity of pipelines. Recently, a study [ 17 ] showed that the tools are effective in acquiring the condition of internal corrosion due to the lack of a scrubber of the dehydration system. However, the relationship between the features of ILI inspection and the effect of CO 2 in the gas pipelines was ignored.…”
Section: Introductionmentioning
confidence: 99%